Strategi Dakwah Muhammadiyah Jawa Barat Era Pandemi Covid-19 - Bambang Saiful Ma'arif; Asep Ahmad Siddiq (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2022)
This study aimed to find out the strategy of preaching Muhammadiyah in West Java in the era of the covid-19 pandemic. The research method uses a qualitative case study approach—data collection techniques through interviews, observations, and document studies. The results showed that Muhammadiyah's da'wah strategy was carried out through consolidation, intensive programs, and communication both internally and externally and using information and communication technology media. Muhammadiyah organizationally designed the message of da'wah to motivate the community to overcome Covid-19. Da'wah strategy is integral between spiritual, intellectual, and physical health, worship, and mu'amalah. Da'wah uses mass media, outdoor media, and social media. The impact of this research can encourage members of the association to get healthy to continue to do activities and work and worship properly.